Crop prediction and soil response to sugarcane straw removal - Satiro, Lucas Santos (2018)
Concerns about global warming and climate change have triggered a growing demand for renewable energy. In this scenario, the interest in using sugarcane straw as raw material for energy production has increased. However, straw plays an important role in maintaining soil quality. In addition, uncertainties as to produced straw amount and the straw removal impact on the stalk yield have raised doubts as to the use this raw material. In this sense, the objective this study was evaluate the short-term (2-year) the sugarcane straw removal impacts on soil and yield modeling of sugarcane stalk and straw, using soil attributes of different layers. Two experiments were carried out in São Paulo state, Brazil: one at Capivari (sandy clay loam soil) and another at Valparaíso (sandy loam soil). We have tested five rates of straw removal (i.e., equivalent to 0, 25, 50, 75 and 100 %). Soil samples were taken from 0-2.5, 2.5-5, 5-10, 10-20 and 20-30 cm layers to analyze pH, total C and N, P, K, Ca, Mg, bulk density and soil penetration resistance. Plant samples were collected to determine the straw and stalk yield. The impacts caused by straw removal differed between the areas, however, they concentrated on the more soil superficial layer. In sandy clay loam soil, straw removal led to organic carbon depletion and soil compaction, while in the sandy loam soil the chemical attributes (i.e. Ca and Mg contents) were the most impacted. In general, the results suggest that straw removal causes reduction more significant in soil quality for the sandy clay loam soil. The results indicate the possibility to remove about half-straw amount deposited on soil\'s surface (8.7 Mg ha-1 straw remaining) without causing severe implications on the quality of this soil. In contrast, although any amount of straw was sufficient to cause alterations the quality of the sandy loam soil, these impacts were less intense and are not magnified with the increase of straw removal. It was possible to model sugarcane straw and stalk yield using soil attributes. The 0-20 cm layer was the most important layer in the stalk yield definition, whereas the 0-5 cm layer, which the impacts caused by the straw removal were concentrated, was less important. Thus, we noticed that impacts caused to soil by straw removal have little influence on crop productivity. Straw prediction has proved more complex and possibly requires additional information (e.g crop and climate information) for good results to be obtained. Overall, the results suggest that the planned removal of straw for energy purposes can occur in a sustainable way, but should take into account site conditions, e.g soil properties. However, long-term research with different approaches is still necessary, both to follow up and confirm our results, and to develop ways to reduce damage caused by this activity.